The study of existing Malay algorithm performed on words beginning with 'D' / Elly Johana Johan - Johan, Elly Johana (2000)
This thesis concerns a Malay language documents retrieval system. Stemming algorithm, database Quran translated documents and electronic root dictionaries are used in order to complete this study. The performance of a Malay stemming algorithm is tested based on words that beginning with 'd', using two experiments. First, use the original set of data collections. Second, the data that have been modified in order to correct the error that exists in database Quran translated documents and in electronic root dictionary. The results of these experiments are based on the 24 order of the rules that consist of prefix, suffix, prefix-suffix pair and infix. The main objective is to minimize the unstemming, understemming, overstemming and other problems that occurred when 'd' words stemmed. It is achieved the objective when the best order of rule to used to stem the words that beginning with 'd' is met. The best rule combinations are 15, 17 and 18. These experiments can serves as a benchmark for future research in Malay language. Furthermore it can help those who are interested to know about certain subject matters from the Al-Quran where the document retrieval system will automatically retrieve all relevant documents in response to the users' queries.